Dilema Posisi Indonesia dalam Persetujuan Paris tentang Perubahan Iklim - Naila Sukma Aisya (Indonesian Perspective, 2019)
Indonesia is currently experiencing a membership dilemma in the Paris Agreement due to the export ban on palm oil imposed by the European Union. In one hand, palm oil commodity is one of the important export commodities for Indonesia. On the other hand, the conversion of forests into oil palm plantations has become a major factor in deforestation and land damage in Indonesia. The repudiation of the United States from the Paris Agreement seemed to provide justification for Indonesia to withdraw from the agreement. This paper attempts to analyze the position of Indonesia in the Paris Agreement using the global environmental ethics approach. This paper argues that Indonesia still needs to maintain its position in the Paris Agreement by considering environmental justice aspects.